Comparative study of the electrochemical behavior and analytical applications of (bio)sensing platforms based on the use of multi-walled carbon nanotubes dispersed in different polymers - Primo, Emiliano Nicolás (2013)
This review present a critical comparison of the electrochemical behavior and analytical performance of glassy carbon electrodes (GCE) modified with carbon nanotubes (CNTs) dispersed in different polymers: polyethylenimine (PEI), PEI functionalized with dopamine (PEI-Do), polyhistidine (Polyhis), polylysine (Polylys), glucose oxidase (GOx) and double stranded calf-thymus DNA (dsDNA). The comparison is focused on the analysis of the influence of the sonication time, solvent, polymer/CNT ratio, and nature of the polymer on the efficiency of the dispersions and on the electrochemical behavior of the resulting modified electrodes. The results allow to conclude that an adequate selection of the polymers makes possible not only an efficient dispersion of CNTs but also, and even more important,the building of successful analytical platforms for the detection of different bioanalytes like NADH, glucose, DNA and dopamine.